Analysis of short-circuit transients in the LHC main dipole circuit. (June 2020) - Liakopoulou, A; Annema, A J; Bortot, L; Charifoulline, Z; Maciejewski, M; Prioli, M; Ravaioli, E; Salm, C; Schmitz, J; Verweij, A P
Abstract: After the occurrence and detection of a short circuit to ground in the LHC main dipole circuit, a fast power abort is triggered and the current in the circuit starts decaying semi-exponentially from a maximum value of 11.85 kA to zero, with a time constant of 103 s. If a short to ground occurs, the current flows through the fuse that is present in the grounding subcircuit. Depending on the value of the thermal load, the fuse first enters a pre-arcing region where it starts intermittently blowing up, until the blow-up threshold is reached, after which it definitively blows up. A simulation scheme utilising a common interface between PSpice and Matlab is proposed in order to simulate the blow-up behaviour of the fuse and hence increase the accuracy of the circuit model for short circuits to ground. A parametric analysis of the short circuit to ground parameters is performed and a better understanding of the behaviour of the circuit under different conditions is obtained. The worst-case values of the voltage to ground in the LHC main dipole circuit are identified for both the case where the intermittent behaviour of the fuse is included in the model as well as for the case where the fuse is not modelled and a comparison between the two is given.